1997
DOI: 10.1111/j.1550-7408.1997.tb05716.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Hybridization by Multilocus Enzyme Electrophoresis and Random Amplified Polymorphic DNA Between Leishmania braziliensis and Leishmania panamensis/guyanensis in Ecuador

Abstract: The taxonomic attribution of four Leishmania stocks isolated from humans in Ecuador has been explored by both multilocus enzyme electrophoresis and random amplified polymorphic DNA. For three loci, MLEE results showed patterns suggesting a heterozygous state for a diploid organism, while the corresponding homozygous states are characteristic of the Leishmania panamensis/guyanensis complex and Leishmania braziliensis, respectively. Other enzyme loci showed characters attributable to either the L. panamensis/ gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
2
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 17 publications
2
41
2
2
Order By: Relevance
“…Notoriously, L. (V.) braziliensis is geographically the species most widespread in the country, having been isolated from CL and MCL patients in nine of 15 surveyed provinces (Armijos et al 1990, Bañuls et al 1999, Furuya et al 1997, Calvopina et al 2001a). In the Amazon region only L. (V.) braziliensis was identified, but hybrid genotypes between L. (V.) panamensis/guyanensis and L. (V.) braziliensis had also been reported (Bañuls et al 1997). Furthermore, Pratlong et al (2002) identified L. naiffi in a German patient with CL suspected to be infected in this region.…”
Section: Parasite Distributionsmentioning
confidence: 94%
See 1 more Smart Citation
“…Notoriously, L. (V.) braziliensis is geographically the species most widespread in the country, having been isolated from CL and MCL patients in nine of 15 surveyed provinces (Armijos et al 1990, Bañuls et al 1999, Furuya et al 1997, Calvopina et al 2001a). In the Amazon region only L. (V.) braziliensis was identified, but hybrid genotypes between L. (V.) panamensis/guyanensis and L. (V.) braziliensis had also been reported (Bañuls et al 1997). Furthermore, Pratlong et al (2002) identified L. naiffi in a German patient with CL suspected to be infected in this region.…”
Section: Parasite Distributionsmentioning
confidence: 94%
“…have been identified from humans, sand flies and non-human mammals (Table). The map ( Bañuls et al (1997Bañuls et al ( , 1999 doubted the separate taxonomic status of the latest two species. L. (L.) amazonensis has been only reported from subtropical Ecuador in human CL (Armijos et al 1990, Furuya et al 1997), but also infecting other mammals (Mimori et al 1989).…”
Section: Parasite Distributionsmentioning
confidence: 99%
“…For example, based on evidence from PFGE analyses, Bañuls et al (8) have proposed the occurrence of pseudorecombination in Leishmania populations. Moreover, several genetic studies indicate genetic recombination between Leishmania individuals, despite lack of evidence for a sexual stage (9)(10)(11)(12)(13)(14)(15)(16). In any case, the molecular data suggest that, after a hybridization event, hybrids propagate clonally in natural populations (9,12).…”
mentioning
confidence: 96%
“…Several past studies have reported co-infection of two parasite species [47], the presence of new parasites species (Le. major-like) [48] and hybrid species in Ecuador [49]; recently Le. naiffi was for the first time found in Ecuador [50] and Lutzomyia tuberculata was for the first time found constituting a new sand fly species record for the country [51], thus the immense biodiversity of parasite and vector species still need to be further investigated.…”
Section: Resultsmentioning
confidence: 99%